ASEAN economic integration. - Fu, Joy Li En. (2009)
The objective of this paper is to investigate the extent of ASEAN integration via four channels: trade, investments, financial and labour. The general methodology employed for trade integration is centered on trade volumes. Whereas analysis on investment integration focuses on the FDI flows. Assessment of financial integration is based on government’s participation in the bond market. As for labour integration, an experimental survey was constructed to gain insights on labour mobility from a worker’s perspective. Compared among the four aspects, this paper finds that trade integration has been the most successful thus far. While financial integration appears to have made the least progress. Nonetheless both investment and labour integration have made moderate advancements. Hence much collective effort among ASEAN member countries will be needed for ASEAN to achieve full integration in future.